2017
DOI: 10.3233/jad-161042
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Applicability of the Montreal Cognitive Assessment (MoCA): A Systematic Review

Abstract: The MoCA is widely used to screen for mild cognitive impairment. While there are many available versions, the cross cultural validity of the assessment has not been explored sufficiently.We aimed to interrogate the validity of the MoCA in a cross-cultural context: in differentiating mild cognitive impairment (MCI) from normal controls (NC); and identifying cut-offs and adjustments for age and education where possible. This review sourced a wide range of studies including case-control studies. In addition, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 59 publications
9
121
0
Order By: Relevance
“…Thirdly, many other studies observed the same or close cutoff scores between 22 and 24 points for MCI in different languages, countries, and cohorts [3, 18, 20, 22, 23, 26, 33, 43]. This is in line with the conclusion and findings of recent reviews that thresholds lower than 26 are likely to be more useful for optimal diagnostic accuracy [9, 18, 25, 43].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Thirdly, many other studies observed the same or close cutoff scores between 22 and 24 points for MCI in different languages, countries, and cohorts [3, 18, 20, 22, 23, 26, 33, 43]. This is in line with the conclusion and findings of recent reviews that thresholds lower than 26 are likely to be more useful for optimal diagnostic accuracy [9, 18, 25, 43].…”
Section: Discussionsupporting
confidence: 78%
“…This is in line with the conclusion and findings of recent reviews that thresholds lower than 26 are likely to be more useful for optimal diagnostic accuracy [9, 18, 25, 43]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Adapting cognitive assessment instruments from HICs to LMIC settings has been criticized as this typically introduces cultural, educational, and literacy biases increasing the risk of misclassification and an overestimation of dementia prevalence . It is further noted that some widely adapted measures lack rigorous psychometric validation across different LMIC settings …”
Section: Instruments To Assess Cognition Adapted From Hicsmentioning
confidence: 99%
“…Low levels of education and literacy have been found to affect performance on numerous cognitive domains including the following: reading, writing, drawing, memory, visual perception, language, verbal fluency, calculating, and reasoning . They also influence brief assessment measures of global cognitive function, including the MMSE, Montreal Cognitive Assessment (MoCa), Addenbrooke's Cognitive Examination (ACE), Clock Drawing Test (CDT), Mini Cog, and 7 Minute Screening, as highlighted from studies conducted in Asia, South America, Africa, and the Middle East . However, some measures, for example, the Rowland Universal Dementia Assessment Scale (RUDAS) that was developed to assess dementia in multicultural populations in Australia, do not require the person to be able to read or write and are less influenced by education compared with other instruments such as the MMSE .…”
Section: Instruments To Assess Cognition Adapted From Hicsmentioning
confidence: 99%